Wolność słowa — ujęcie prawnokarne - Płatek, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The text refers to relations between freedom of speech and criminal law. It examines the ratio behind limiting the freedom of expression when personal psychological harm might occur. The inspiration is drawn from Professor Tomasz Kaczmarek’s works on the axiology of criminal law. The ratio of criminal law and ratio of democratic legal state is tested within freedom of speech. Article 196 of criminal law, among the others, is critically reviewed as far as its rationale for being included in the criminal law vis-à-vis Article 212 of criminal law and constitutional provisions confirming freedom of speech as the human right.
Keywords: wolność słowa; uczucia religijne; aksjologiczne podstawy prawa karnego